POLICY IMPLEMTATION “LONTONG KUPANG” ONLINE AND INTEGRATED SERVICE ONE GATE SYSTEM: (Study: Department Of Population and Civil Registration Surabaya City) - Ajiputra, Rendy Fadila; Handoko, V. Rudy (DIA: Jurnal Administrasi Publik, 2024)
Lontong Kupang (Online and Integrated Services Through One Gate System Between Disdukcapil Surabaya, Surabaya Religious Court and Ministry of Religion Surabaya). The purpose of this research is to analyze the successful implementation of the Lontong Kupang program based on the Theory of Program Implementation Success according to George Edward III which consists of Communication, Disposition, Resources and Bureaucracy Structure. The method used in this study is descriptive qualitative with observation and interview data collection. The research results show that the Lontong Kupang Program has been successful and the implementation is good. However, in its implementation there are still several obstacles that hinder the implementation of the program. The inhibiting factors found in this research are the lack of budget availability for program implementation, and the lack of outreach to the community regarding the Lontong Kupang service program which results in many people not understanding the requirements or documents that must be brought when registering.